ABC of medical law - Corfield, Lorraine , 1971-; Granne, Ingrid; Latimer-Sayer, William (ABC series, 2009)
Provides a basic introduction to the legal issues faced in health care. This work offers coverage of the legal issues to be found in daily medical practice, including confidentiality, research, consent, negligence, organ donation and human rights, as well as more contentious issues such as tissue retention and withholding/withdrawing treatment.